(untitled) (Research, Society and Development, 2022)
Varicose ulcers can be considered a public health problem, taking into account the damage caused to the life of the individual and their increasing incidence in society. Its occurrence generates skin deformities, causing great discomfort, losses in self-esteem, social life and even psychosocial disorders. Objective: to describe the quality of life of patients with venous ulcers and the damage caused by this condition, with the aim of emphasizing the theme and promoting knowledge about the same. Method: integrative literature review, which was searched through Scielo databases; Medline, BENF, lilacs, using the descriptors in health sciences: quality of life/quality of live, varicose ulcers/varicose ulcers. The research took place between April and June 2022. As inclusion criteria, studies from 2012-2022 were selected, in English, Portuguese and Spanish, which were available in full. The evidence included 10 selected articles, 5 of which were national and 5 international with a broad aspect of methodological and investigative approach. Results: Based on the articles included in the research, the damage caused by the lesion was observed, the quality of life score of patients with venous ulcers is lower, when compared to those without ulcers, their functional capacity is highlighted, becoming impaired as well as self-esteem, social and psychosocial factors. Final considerations: Understand the lifestyle and its particularities in the health care of the person with varicose ulcer, aiming at contributing to the expansion of studies focused on this theme, favoring the training and information of nurses, providing the improvement of their knowledge, proposing the rather a holistic and integral assistance.